If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 7x + -28 = 2x^{2}+ -8x + -3x + 12 Reorder the terms: -28 + 7x = 2x^{2}+ -8x + -3x + 12 Reorder the terms: -28 + 7x = 12 + -8x + -3x + 2x^{2}Combine like terms: -8x + -3x = -11x -28 + 7x = 12 + -11x + 2x^{2}Solving -28 + 7x = 12 + -11x + 2x^{2}Solving for variable 'x'. Reorder the terms: -28 + -12 + 7x + 11x + -2x^{2}= 12 + -11x + 2x^{2}+ -12 + 11x + -2x^{2}Combine like terms: -28 + -12 = -40 -40 + 7x + 11x + -2x^{2}= 12 + -11x + 2x^{2}+ -12 + 11x + -2x^{2}Combine like terms: 7x + 11x = 18x -40 + 18x + -2x^{2}= 12 + -11x + 2x^{2}+ -12 + 11x + -2x^{2}Reorder the terms: -40 + 18x + -2x^{2}= 12 + -12 + -11x + 11x + 2x^{2}+ -2x^{2}Combine like terms: 12 + -12 = 0 -40 + 18x + -2x^{2}= 0 + -11x + 11x + 2x^{2}+ -2x^{2}-40 + 18x + -2x^{2}= -11x + 11x + 2x^{2}+ -2x^{2}Combine like terms: -11x + 11x = 0 -40 + 18x + -2x^{2}= 0 + 2x^{2}+ -2x^{2}-40 + 18x + -2x^{2}= 2x^{2}+ -2x^{2}Combine like terms: 2x^{2}+ -2x^{2}= 0 -40 + 18x + -2x^{2}= 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-20 + 9x + -1x^{2}) = 0 Factor a trinomial. 2((-5 + x)(4 + -1x)) = 0 Ignore the factor 2.## Subproblem 1

Set the factor '(-5 + x)' equal to zero and attempt to solve: Simplifying -5 + x = 0 Solving -5 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + x = 0 + 5 x = 0 + 5 Combine like terms: 0 + 5 = 5 x = 5 Simplifying x = 5## Subproblem 2

Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4## Solution

x = {5, 4}

| y=x^2+5x | | y=x^2+2x | | x^7-5x^5+x^2-5=0 | | 15x^2-8x-7=0 | | X^2+6x-27=0 | | 3x^2-6x+12=0 | | (4x^3-6x^2+5)-(8x^2+3x-6)= | | 11x^2-2x+9=0 | | 4x(2x^2-6x-5)= | | 10x^2+5x+8=0 | | 9x^2+9x+8=0 | | 12x^2+5x+10=0 | | 9x^2+21x+12=0 | | -2x^2+4x+12=0 | | 3x^2+10x+8=0 | | -8x^2+8x-2=0 | | X^2-x-2=0 | | 3x^2+x-1=0 | | (8x^4+5x^3-5)-(5x^2-6x+4)= | | 2x^2+10x+12=0 | | (7m^8-5m^3+9m^2+5)+(9m^7+3m^3-4m)= | | X^2-5x-48=0 | | X^2-12x+20=0 | | x^4-4x^3+5x^4-9x^3+2= | | (6x^4y^3+9x^3y^2)+(3x^3y^3-2x^3y^2-7xy)= | | y=x^3+3x^2-9x-8 | | 4x^4+3x^2-1=0 | | kx^2+4x+(5-k)=0 | | 12a^4b^3=0 | | 108x^4+360x^3+447x^2+245x+50=35 | | -35x^2-5x+30=0 | | 12x+2=3x^2 | | 2x^2+3x+5=0 | | (12x^2-3x-8)-(4x^2+5)= | | 5n+6n^4+3n-8n^4+n= | | 3n-2n^4+n+7n^4-2n= | | 12n-2n^4-10n-2n^4+n= | | X^2+16x+42=0 | | x^2+2x-288=0 | | 2x^2+3x-44=0 | | X^2+10x+22=6 | | x^5+x^4+x^3+x^2+x+3=0 | | x^2+6x-65=0 | | 56x+8x^2=0 | | x^2+6x+8=0 | | x^2+16x=-7 | | 3x^2-24x+1=0 | | 5x^2+6xy+13j^2= | | 2x^2+14x=120 | | 6r^2+11r-10=0 | | 6r^2+10r=0 | | y=4k^2+6k-1 | | 3x^2+16x+64=0 | | 2x^2+8x=90 | | 3x^2+12x=180 | | 4x^2+13x-75=0 | | 4x^2+13-75=0 | | 3x^2+10x-88=0 | | 2v^2-4v+52= | | v^2-4v+16= | | v^2-36= | | 24uxy^5-22u^5y^5= | | 4u^6+6u^5-10u^4= | | 10x^2+12x+18=0 | | 25p^2=4 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions